Hematologic profile of leprosy patients in reactional episode of erythema nodosumleprosum - Freitas, Telma Cristina de (1999)
In this work, eighteen patients in reactional episode of erythema nodosum leprosum (ENL) had their hematologic paramaters evaluated. Eight of these patients had intense and moderate ENL, and ten patients had mild ENL. The results showed that patients with intense and moderate ENL had significant alterations in the hematologic findings: iron deficiency, an increased euglobulin lysis time and hyperfibrinogenemia. Nevertheless, no alteration was observed in the other parameters studied (prothrombin time, Heinz body and fibrinogen degradation products), in all the cases of ENL.